REPRODUKSI WOMANHOOD DALAM NOVEL BUNDA: KISAH CINTA 2 KODI KARYA ASMA NADIA - Udasmoro, Wening (Adabiyyāt: Jurnal Bahasa dan Sastra, 2017)
Positioning women in literary works by women’s writers almost always has a dynamic turn. Asma Nadia, as a women’s writer is a representation of Forum Lingkar Pena which tends to flip the early women’s narrative model in Reformation era. This narrative model positions women, who are as if in a autonomus and auto-regulative narrative, into their subordinative position. The reversal of women’s narration by women’s writer with the religious perspectives brings up questions like: how is the positioning represented? How are the construction and the position of women in the turning point of the Reformation? What kind of reproduction of womanhood is formed in the novel? This paper aims at investigating the construction of womanhood in the novel with the religious perspectives by Asma Nadia, Bunda Kisah Cinta 2 Kodi. The alternatives in facing the religious structures are negotiated by the writers in various ways. Pardoxes emerge as the consequences of those alternatives.